PEMBUATAN POJOK BACA SEBAGAI UPAYA PENGUATAN BUDAYA LITERASI SISWA DI SDN KULEM, DESA PENGONAK, PRAYA TIMUR - Hakimi, Muhammad; Jurnal Wicara; Sukmarani, Ni; Prabawati, Putu; Dharma, I; Wulandari, Alfira; Sofiana, Dina; Febina, Putri; Kanti, Putri; Abdianzah, Muhammad; Afuw, Afiifah (Jurnal Wicara, 2025)
The Community Service Program (KKN) is one form of student service to the community, aiming to make a tangible contribution to improving the quality of education. The KKN activity carried out at SDN Kulem, Pengonak Village, East Praya District, was focused on implementing a reading corner as an effort to strengthen students' literacy culture. The main objectives of this activity are to cultivate reading interest and familiarize students with the reading materials available at school. The problem of low reading interest among students necessitates innovative learning spaces that are engaging, easily accessible, and tailored to children's needs. The method used is the creation of a reading corner in the classroom, utilizing the school's existing facilities and reading collection. The results of the implementation show a positive response from the students, indicated by their increased enthusiasm in utilizing the reading corner as a means of reading outside of class hours. The implementation of reading corners has proven effective as a strategic effort in building a school ecosystem that supports literacy, while also being a concrete step in fostering a reading culture from an early age.